Telemedicine: International Law Comparison - Aris Prio Agus Santoso; Soares, Domingos; Fauzi, Fazlin; Amallia, Sabrina Difa (Eastasouth Institute, 2024)
The main problems in telemedicine include the lack of uniformity in international regulations, limited technological infrastructure in some countries, and data protection and patient privacy. Additionally, legal responsibilities and malpractice risks have not been standardized. Gaps in access to services, especially in remote areas, and ethical challenges and quality standards are also obstacles. The purpose of this research is to find out international legal considerations regarding the use of Telemedicine and find solutions to overcome Telemedicine legal issues. This research uses a normative juridical approach with an emphasis on comparative studies. The results of the research were then analyzed qualitatively. Based on research results, show that Telemedicine is regulated differently in various countries. In Indonesia, it is regulated by Minister of Health Regulation Number 20 of 2019 for diagnosis, treatment, and continuing education with service costs borne by the health facility. Malaysia has a Telemedicine Act 1997, focused on follow-up care and drug prescriptions, growing rapidly in the private sector during the COVID-19 pandemic. Argentina published telehealth guidelines in 2019 and 2022, requiring health insurance companies to adopt teleconsultation platforms. Austria through the TeleHealth Commission since 2013 regulates telemonitoring, teletherapy, teleconciliation, and teleconferencing with strict data protection laws. Mexico integrates telehealth in general health services, regulated by IMSS and ISSSTE, while Russia regulates through the Health Protection Law with strict IT requirements. International telemedicine legal solutions require harmonization of regulations, personal data protection, information security standards, recognition of professional licenses, dispute resolution mechanisms, and legal liability regulations. Education and public awareness are essential to overcome these challenges, supported by international cooperation that strengthens the global legal infrastructure of telemedicine.